Identification of galectins as novel regulators of platelet signaling and function - Romaniuk, María Albertina (2011)
Platelet activation at sites of vascular injury leads to the formation of a hemostatic plug. Activation of platelets is therefore crucial for normal hemostasis. However, uncontrolled platelet activation may also lead to the formation of occlusive thrombi that can cause ischemic events. Platelets can be activated by soluble molecules including thrombin, TXA 2, adenosine diphosphate (ADP), and serotonin or by adhesive extracellular matrix (ECM) proteins such as von Willebrand factor and collagen. In this article, we review recent advances on the role of galectins in platelet physiology. By acting in either soluble or immobilized form, these glycan-binding proteins trigger platelet activation through modulation of discrete signaling pathways. We also offer new hypotheses and some speculations about the role of platelet-galectin interactions not only in hemostasis and thrombosis but also in inflammation and related diseases such as atherosclerosis and cancer. © 2011 IUBMB.